2018
DOI: 10.1002/jmri.25945
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of myocardial involvement by T1 mapping of cardiac MRI in idiopathic inflammatory myopathy

Abstract: 2 Technical Efficacy: Stage 3 J. MAGN. RESON. IMAGING 2018;48:415-422.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
(35 reference statements)
2
19
0
Order By: Relevance
“…Techniques using at least two acquisitions with different flip angles are commonly used for this purpose 32 but other techniques have also been evaluated in order to further optimize the accuracy of T1 mapping 33 . Furthermore, pathological tissue alterations as a result of disease processes such as extracellular matrix expression and tissue fibrosis can be noninvasively visualized and quantified based on changes in T1 relaxation properties 13,14,34,35 . Few studies have already evaluated non-contrast-enhanced T1 mapping for the diagnosis of PCa using different technical approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Techniques using at least two acquisitions with different flip angles are commonly used for this purpose 32 but other techniques have also been evaluated in order to further optimize the accuracy of T1 mapping 33 . Furthermore, pathological tissue alterations as a result of disease processes such as extracellular matrix expression and tissue fibrosis can be noninvasively visualized and quantified based on changes in T1 relaxation properties 13,14,34,35 . Few studies have already evaluated non-contrast-enhanced T1 mapping for the diagnosis of PCa using different technical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, any further use of MOLLI for prostate imaging has not been reported yet. T1 measured with MOLLI has proven to be a robust imaging biomarker in cardiac MRI 13,14 as well as selected malignancies such as renal cell cancer with an excellent interreader agreement 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical manifestations of cardiac involvement in IIM patients can range from none to arrhythmia, heart failure, and even cardiac death [5]. Previous studies have found cardiac involvement manifesting as diastolic dysfunction or decreased longitudinal strain by echocardiography [6,7], abnormalities on electrocardiography (ECG) [6], presence of myocardial late gadolinium enhancement (LGE) [3,8,9], increased myocardial T1and T2 values [10][11][12], and increased extracellular volume (ECV) [13] by cardiovascular magnetic resonance (CMR). Although a few previous studies have reported the potential value of multiparametric CMR techniques in identifying cardiac involvement in patients with IIM [10,11], there is still a lack of dynamic monitoring of myocardial histological changes during therapy.…”
mentioning
confidence: 99%
“…Native T1 increases may indicate disease and have been associated with diffuse myocardial fibrosis in different types of cardiomyopathy [7–15]. Moreover, in patient groups with myocardial impairment, an increase of native T1 was observed in the absence of late gadolinium enhancement (LGE) [7, 9, 10, 14, 15] suggesting that native T1 mapping can be an early indicator of myocardial tissue abnormality. Therefore, a robust native T1 quantification method is needed to ensure early identification of heart function abnormality.…”
Section: Introductionmentioning
confidence: 99%